PROFESSIONAL COMPETENCE STRUCTURE OF FUTURE BACHELORS OF RAILWAY TRANSPORT IN PROFESSIONAL TRAINING - Hrebenyk, A. (Physical and Mathematical Education, 2021)
Under intensive living and production conditions, questions increasingly arise not so much about the content of knowledge acquired by students, but about highly effective methods, forms, means of professional competence formation as the professional training important component. This article raises the issue of the professional competence formation of future railway transport specialists in the professional training. The scientific publications on the research topic are analyzed and the professional competence structural components of future bachelors’ in this field are identified.Formulation of the problem. Nowadays, more and more employers are not fully satisfied with the specialists’ training. As a result, there is a significant reform of the educational sector. Special attention is paid to the issues of professional training. Thus, the professional competence formation of the future specialist is a relevant and important issue. And the question of the professional competence structure of future specialists, including future bachelors of railway transport, needs a detailed study. Materials and methods. In the scientific process, dissertation research materials, pedagogical and scientific literature were used. To achieve the goal of the study theoretical and empirical methods: analysis and systematization; observation; written and oral interview; analysis, systematization, generalization were used.Results. Thus, the professional competence components of future bachelors of railway transport are identified, namely: motivational-value, personal-functional, reflexive-evaluative.Conclusions. The proposed professional competence structure of future bachelors of railway transport is singled out taking into account the professional competence content and these specialists’ professional activity features. Structuring the category “professional competence of future bachelors of railway transport” can positively affect the organization level of this competence formation process in students in the training process and the process quality of its formation diagnosing level. Further research is needed on the model development of this process and its organizational and methodological support.
Keywords: professional training; professional competence; components; bachelor of railway transport; professional